The effect of medication therapy management service combined with a national PharmaCloud system for polypharmacy patients. Issue 134 (October 2016) - Chen, Chang-Ming; Kuo, Li-Na; Cheng, Kuei-Ju; Shen, Wan-Chen; Bai, Kuan-Jen; Wang, Chih-Chi; Chiang, Yi-Chun; Chen, Hsiang-Yin
Highlights: The study built up a new model by using Taiwan National Health Insurance Administration PharmaCloud system to facilitate medication reconciliation for pharmacists in the medication therapy management service. The model improved the patients' attitude and practices on rational use of medication as well as compliance to medication by the intervention. Phone follow-ups showed that the patients' practice and compliance scores on medication use were significant improved three months after the intervention. Abstract: Background: This study evaluated a medication therapy management service using the Taiwan National Health Insurance Administration's PharmaCloud system in a medical center in Taiwan. The new PharmaCloud System, launched in 2013, links a complete list of prescribed and dispensed medication from different hospitals, clinics, and pharmacies for all insured patients. Method: The study included patients with polypharmacy (≥5 drugs) at a medication therapy management service from March 2013 to March 2014. A structured questionnaire was designed to collect patients' baseline data and record patients' knowledge, attitudes, and practice scores before and after the service intervention. Phone follow-ups for practice and adherence scores on medication use were performed after 3 months. Results: There were 152 patients recruited in the study. Scores for medication use attitudes and practice significantly increased after the service (attitudes: 40.06 ± 0.26 to 43.07 ± 0.19, p  <   0.001; practice: 33.42 ± 0.30 to 40.37 ± 0.30, p  <   0.001). The scores for medication adherence also increased from 3.02 ± 0.07 to 3.92 ± 0.02 ( p  <   0.001). Conclusions: The PharmaCloud system facilitates accurate and efficient medication reconciliation for pharmacists in the medication therapy management service. The model improved patients' attitudes and practice of the rational use of medications and adherence with medications. Further studies are warranted to evaluate human resources, executing costs, and the cost-benefit ratio of this medication therapy management service with the PharmaCloud system.